Asymptotic Criteria of Neutral Differential Equations with Positive and Negative Coefficients and Impulsive Integral Term - Mohamad, Hussain Ali; Jaddoa, Aqeel (Iraqi Journal of Science, 2020)
In this paper, the asymptotic behavior of all solutions of impulsive neutral differential equations with positive and negative coefficients and with impulsive integral term was investigated. Some sufficient conditions were obtained to ensure that all nonoscillatory solutions converge to zero. Illustrative examples were given for the main results.